2016
DOI: 10.15171/jcvtr.2016.04
|View full text |Cite
|
Sign up to set email alerts
|

Radial left ventricular dyssynchrony by speckle tracking in apical versus non apical right ventricular pacing- evidence of dyssynchrony on medium term follow up

Abstract: Introduction: To study effects of various sites of right ventricular pacing lead implantation on left ventricular function by 2-dimensional (2D) speckle tracking for radial strain and LV dyssynchrony. Methods: This was retrospective prospective study. Fifteen patients each with right ventricular (RV) apical (RV apex and apical septum) and non-apical (mid septal and low right ventricular outflow tract [RVOT]) were programmed to obtain 100% ventricular pacing for evaluation by echo. Location and orientation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
4
0
3
Order By: Relevance
“…The effects of right ventricular septal pacing in terms of maintaining ventricular synchrony and cardiac function are still controversial. [13][14][15][16][17][18] With the rapid development of technology, many studies have confirmed the advantage of left bundle branch area pacing. Studies proved that left bundle branch area pacing produces narrower-paced QRS duration and better echocardiographic cardiac function than does right ventricular septal pacing.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of right ventricular septal pacing in terms of maintaining ventricular synchrony and cardiac function are still controversial. [13][14][15][16][17][18] With the rapid development of technology, many studies have confirmed the advantage of left bundle branch area pacing. Studies proved that left bundle branch area pacing produces narrower-paced QRS duration and better echocardiographic cardiac function than does right ventricular septal pacing.…”
Section: Discussionmentioning
confidence: 99%
“…Již po mnoho let je známo, že apikální pravokomorová stimulace může vést k indukci systolické dysfunkce levé komory (LK) a k rozvoji manifestního srdečního selhání. Patofyziologickým podkladem je nefyziologická aktivace kontrakce z hrotové oblasti vedoucí k inter-a intraventrikulární dyssynchronii, remodelaci LK a levé síně (LS) a možnému vzniku fi brilace síní [1][2][3][4]. Stimulací indukova-ná dysfunkce LK se může vyskytnout až u 50 % pacientů plně nebo částečně závislých na pacingu.…”
Section: úVodunclassified
“…Provedené vyšetření prokázalo, že elektroda není ve skutečnosti zavedena do midsepta, ale do přední stěny PK (v anteroseptálním žlábku) a že hrot elektrody je v těsné vzdálenosti, tedy méně než 5 mm, od RIA. Následná kontrola rametry inter-a intraventrikulární dyssynchronie) během septální stimulace ve srovnání s apikální stimulací [3,8,10].…”
Section: úVodunclassified
“… 5–9 However, short term, echocardiographic parameters of synchronization and related QRS duration were significantly better during septal stimulation compared to apical stimulation. 3 , 8 , 10 In one randomized study of patients with reduced ejection fraction (<45%), septal pacing was associated with better preservation of systolic function compared to apical pacing. 10 …”
Section: Introductionmentioning
confidence: 99%